Zinc Oxide Nanoparticles Blended Polyethersulfone Ultrafiltration Membranes - Madenli, Evrim Çelik; Şen, Fulya; Erçin, Ahmet (Fırat University, 2023)
Membranes are widely used in the food industry, petrochemical industry, energy industry as well as water and wastewater treatment due to their high removal efficiency and low cost. However, the main disadvantage of membrane applications is fouling. One of the methods used to prevent membrane fouling is to increase membrane hydrophilicity. Membrane hydrophilicity can be increased by using additives during membrane synthesis. Zinc oxide nanoparticles (nZnO) are one of the interesting nanoparticles with their high surface-to-volume ratio and low cost. nZnO were used as additives in polyethersulfone (PES) membranes in this study. nZnO doped PES (P/Z) membranes were prepared using the phase inversion method. Prepared membranes were characterized using water contact angle, Fourier Transform Infrared Spectrometer (FTIR), and Scanning Electron Microscopy (SEM). Pure water filtration performance and protein removal efficiency of the prepared membranes were also investigated. The results of this study show that the addition of nZnO increased the hydrophilicity, porosity, pure water flux, protein removal efficiency and the fouling resistance of the PES membranes.

Membranlar gıda, petrokimya, enerji endüstrilerinin yanı sıra yüksek giderim verimi ve düşük maliyeti nedeniyle su ve atık su arıtımında da yaygın olarak kullanılmaktadır. Fakat, membran uygulamalarında karşılaşılan en büyük sorun membran tıkanmasıdır. Membran tıkanmasını azaltmak için kullanılan yöntemlerden bir tanesi membran hidrofilikliğinin arttırılmasıdır. Membran sentezi sırasında membran hidrofilikliğini arttıracak katkı maddeleri eklenmesi ile membran hidrofilikliği arttırılabilmektedir. Yüksek yüzey / hacim oranı ve düşük maliyeti ile çinko oksit nanoparçacıkları (nZnO) ilgi çeken nanoparçacıklardan biridir. Bu çalışmada nZnO, polietersülfon (PES) membranlarda katkı maddesi olarak kullanılmıştır. nZnO katkılı PES (P/Z) membranlar faz geri çevrilmesi yöntemi kullanılarak hazırlanmıştır. Hazırlanan membranlar temas açısı, Fourier Dönüşümlü Kızıl Ötesi Spektrometresi (FTIR), Taramalı Elektron Mikroskobu (SEM) kullanılarak karakterize edilmiştir. Hazırlanan membranların saf su filtrasyonu ve protein giderim verimleri de incelenmiştir. Elde edilen sonuçlara göre nZnO ilavesi PES membranların hidrofilikliğini, porozitesini, saf su akısını, protein giderim verimini ve tıkanma direncini arttırmıştır.
Çinko Oksit Nanoparçacıkları Katkılı Polietersülfon Ultrafiltrasyon Membranlar
Keywords: Environmental Engineering (Other); Çevre Mühendisliği (Diğer)